Bimetallic Zinc-Iron-Modified Sugarcane Bagasse Biochar for Simultaneous Adsorption of Arsenic and Oxytetracycline from Wastewater - Nhat-Thien Nguyen; An-Bang Lin; Chang-Tang Chang; Gui-Bing Hong (Molecules, 2025)
Arsenic (As), a highly toxic and carcinogenic heavy metal, poses significant risks to soil and water quality, while oxytetracycline (OTC), a widely used antibiotic, contributes to environmental pollution due to excessive human usage. Addressing the coexistence of multiple pollutants in the environment, this study investigates the simultaneous adsorption of As(III) and OTC using a novel bimetallic zinc-iron-modified biochar (1Zn-1Fe-1SBC). The developed adsorbent demonstrates enhanced recovery, improved adsorption efficiency, and cost-effective operation. Characterization results revealed a high carbon-to-hydrogen ratio (C/H) and a specific surface area of 1137 m2 g−1 for 1Zn-1Fe-1SBC. Isotherm modeling indicated maximum adsorption capacities of 34.7 mg g−1 for As(III) and 172.4 mg g−1 for OTC. Thermodynamic analysis confirmed that the adsorption processes for both pollutants were spontaneous (ΔG < 0), endothermic (ΔH > 0), and driven by chemical adsorption (ΔH > 80 kJ mol−1), with increased system disorder (ΔS > 0). The adsorption mechanisms involved multiple interactions, including pore filling, hydrogen bonding, electrostatic attraction, complexation, and π-π interactions. These findings underscore the potential of 1Zn-1Fe-1SBC as a promising adsorbent for the remediation of wastewater containing coexisting pollutants.